Giải bất phương trình sau : `(x+3)(2x-6)<0`

Question

Giải bất phương trình sau :
`(x+3)(2x-6)<0`

in progress 0
Arya 2 tuần 2021-09-09T13:53:02+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-09-09T13:54:05+00:00

    `\text{~~Holi~~}`

    `(x+3)(2x-6)<0`

    `->`\(\left[ \begin{array}{l}\begin{cases}x+3<0\\2x-6>0\end{cases}\\\begin{cases}x+3>0\\2x-6<0\end{cases}\end{array} \right.\) 

    `->`\(\left[ \begin{array}{l}\begin{cases}x<-3\\x>3\end{cases}\\\begin{cases}x>-3\\x<3\end{cases}\end{array} \right.\) 

    `->`\(\left[ \begin{array}{l}x\in∅\\x\in(-3,3)\end{array} \right.\) 

    `-> -3<x<3`

    Vậy nghiệm của bất phuong trình là `{x|-3<x<}3`

    0
    2021-09-09T13:54:08+00:00

    Đáp án:

    `(x+3)(2x-6)<0`

    `<=>2(x+3)(x-3)<0`

    `Giả` `sử`  `x+3>0 ;x-3<0`

    `Ta` `có`

    \(\left[ \begin{array}{l}x+3>0\\x-3<0\end{array} \right.\) 

    `<=>`\(\left[ \begin{array}{l}x>-3\\x<3\end{array} \right.\) 

    Vậy `-3<x<3`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )